Runt - Bauer, Marion Dane. (New York : Yearling, 2004)
Runt, the smallest wolf cub in the litter, seeks to prove himself to his father King and the rest of the pack and to earn a new name.
Keywords: Wolves -- Juvenile fiction; Wolves -- Fiction